Тенденція розвитку сучасного етнографічного музейництв а півдня України - Величко, Т. (Народна творчість та етнографія, 2008)
In the article the tendencies in development of current ethnographical museum art are covered. To illustrate those, the author provides as the examples the activities of museums in the southern Ukraine. The author pays considerable attention to innovative methods in activities of the present-day museums, shows the role played by the museums in the process of ethno-cultural renaissance of the poly-ethnic population of the region.